FAKTOR-FAKTOR YANG MEMPENGARUHI NILAI NTN PADA NELAYAN ARTISANAL DI PPN PEKALONGAN - Abdul Kohar Mudzakir; Azis Nur Bambang; Imam Triarso (JURNAL PERIKANAN DAN KELAUTAN, 2021)
The low level of welfare of small fishermen is a problem that still cannot be solved. To get an overview of changes in fishermen's welfare quickly, an instrument that is easy to use and can fully describe the welfare of fishermen is needed. The fisherman's exchange rate can be used as an indicator based on the KKP guidelines in measuring the welfare of fishermen. Pekalongan City is one of the coastal areas with high resource potential, especially in the fisheries sector. One of the fishing ports in Pekalongan City is Pekalongan NFP, where the majority of fishermen are still classified as small fishermen. The picture of fishermen's welfare is closely related to the socio-economic conditions in the area. This study aims to determine the factors that influence the fisherman's exchange rate as an indicator of the welfare of artisanal fishermen in the NFP (Nusantara Fisheries Port) Pekalongan. The data used in this study are primary data and secondary data. Primary data were collected through questionnaires to respondents. Secondary data were collected through the desk study method in journals, articles, and books related to this research. The sampling technique used is purposive sampling where 159 people are taken as samples, the number of samples then becomes 130 people due to the elimination of outlier data as many as 29 people. Data analysis was performed using descriptive methods and multiple linear regression. Based on regression analysis, the results of this study found that age, education, total income, and total expenditure are factors that affect artisanal NTN in NFP Pekalongan.